2002
DOI: 10.1021/np020289t
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Inhibitors from Plants:  Isolation, Structure Elucidation, and SAR Studies

Abstract: Fatty acid synthase (FAS) has been identified as a potential antifungal target. FAS prepared from Saccharomyces cerevisiae was employed for bioactivity-guided fractionation of Chlorophora tinctoria,Paspalum conjugatum, Symphonia globulifera, Buchenavia parviflora, and Miconia pilgeriana. Thirteen compounds (1-13), including three new natural products (1, 4, 12), were isolated and their structures identified by spectroscopic interpretation. They represented five chemotypes, namely, isoflavones, flavones, biflav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 40 publications
1
75
0
2
Order By: Relevance
“…Sobre as espécies P. guianensis e D. excelsa ainda não se tem dados, mas B. parviflora apresenta compostos como isoflavonas, flavonas, biflavonóides, derivados hidrolisados de taninos e triterpenóides (Li et al, 2002). Neste caso, os resultados observados demonstram que a atividade termicida ou de repelência dos extrativos poderiam ser atribuídas à atuação de alguns desses compostos, especialmente dos terpenos.…”
Section: Estudos De Propriedades Antitermíticas De Extratos Brutos Deunclassified
See 1 more Smart Citation
“…Sobre as espécies P. guianensis e D. excelsa ainda não se tem dados, mas B. parviflora apresenta compostos como isoflavonas, flavonas, biflavonóides, derivados hidrolisados de taninos e triterpenóides (Li et al, 2002). Neste caso, os resultados observados demonstram que a atividade termicida ou de repelência dos extrativos poderiam ser atribuídas à atuação de alguns desses compostos, especialmente dos terpenos.…”
Section: Estudos De Propriedades Antitermíticas De Extratos Brutos Deunclassified
“…Diante disso, a eficiência de vários compostos vegetais há muito tem sido avaliada, visando encontrar substâncias que possam ser empregadas na formulação de produtos preservantes de madeira, que apresentem não somente a eficiência como também menor dano ao meio ambiente (Logan et al, 1990;Lajide et al, 1995;Nascimento et al, 1999Nascimento et al, , 2000Blaske & Hertel, 2001;Li et al, 2002).…”
Section: Introductionunclassified
“…A number of flavonoids have been shown to inhibit both fungal and human FAS-I (Li & Tian, 2004;Li et al, 2002;Wang et al, 2003). Flavonoids comprise a large group of polyphenolic secondary metabolites that are widespread throughout the plant kingdom (Koes et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported that isoflavones, favones, biflavonoids, hydrolysable tannin-related derivatives, and triterpenoids from plants showed FAS inhibitory activity in vitro. 27) We have reported that feeding of tea catechins, rich in (À)-epigallocatechin gallate and (À)-epicatechin gallate, resulted in visceral fat deposition through a reduction of hepatic FAS activity in Sprague-Dawley rats. 28) In addition, Murase et al reported that green tea extract, which contains high levels of polyphenolic compounds, increased fatty acid beta-oxidation in the liver and muscles of mice.…”
mentioning
confidence: 97%